Controlling w jednostkach administracji publicznej - Stuglik, Joanna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
In the paper the author presents the controlling in the unit of public administration. This material presents problems and directions of development of public management in the world, Europe and Poland briefly. Role, place and functions of controlling in the unit of public administration have been signaled in farthest part. Principles of project designs of controlling process in unit of public administration have been presented in the finally part of article briefly. This paper it is short attempt of signaling of question is presented abstract only. This subject - controlling in the unit of public administration - seems on interesting so many, that it will be present and will be object of widest research. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 406-414